The Effect of Gamification Strategies on Mathematics Learning Outcomes Is Reviewed Based on Self-Efficacy - Jurani, Jurani; Nuh, Muhammad (Prima: Jurnal Pendidikan Matematika, 2025)
This study aims to explain the interaction between the gamification strategy and the level of self-efficacy on students' mathematics learning outcomes. This research uses a quantitative method with a quasi-experimental design and two-way analysis of variance (ANOVA). The population of this study consists of all eighth-grade classes at Mts Al Ittihadiyah, and the research sample consists of students from classes VIII-1 and VIII-2, selected using Cluster Random Sampling technique. The results show that the gamification strategy has a significant impact on mathematics learning outcomes, particularly for students with high self-efficacy. Students who used the Kahoot-assisted gamification strategy showed better learning outcomes compared to those who used the PowerPoint-assisted gamification strategy. The two-way analysis of variance (ANOVA) revealed a significant interaction effect between the gamification strategy and self-efficacy on learning outcomes. The R-squared value of 0.870 indicates that this model explains 87% of the variation in students' learning outcomes. The conclusion of the study shows that the Kahoot-assisted gamification strategy contributes more significantly to improving mathematics learning outcomes compared to PowerPoint, especially for students with high self-efficacy. The results indicate that students with high self-efficacy tend to have better learning outcomes compared to students with low self-efficacy. The findings also show a significant interaction between the gamification strategy and self-efficacy, where the Kahoot strategy is more effective for students with high self-efficacy. There were no significant differences in the effectiveness of the two strategies for students with low self-efficacy